Coordination of electrical drilling machines in open-pit mines: a constraint programming approach - Mohamed Maftah (22428761) (2025)
This article addresses the efficient coordination of multiple electrical drill rigs in open-pit mines, considering unique constraints such as continuous power supply, dynamic obstacle creation, and safe distancing. The objective is to maximise drilling within a given time horizon. This paper provides a comprehensive problem description and proposes a constraint programming model complemented by a heuristic algorithm. Experimental results demonstrate the model’s effectiveness in scheduling up to 300 tasks with 3 machines over 24 hours, achieving near-optimal solutions within 2 minutes. For instances with fewer than 250 tasks, the model consistently reaches optimal solutions, enabling real-time decision-making in dynamic mining environments.